Pharmacotherapeutic considerations of selective estrogen receptor modulators for vascular protection - Al Banna, Janette; Karam, Farah; Hassanieh, Dalia; Khanafer, Youssuf H.; Seed Ahmed, Mohammed; Sharara, Hussein; Eid, Ali H. (Frontiers in Pharmacology, 2026)
Selective estrogen receptor modulators (SERMs) are nonsteroidal compounds that exert context-dependent agonist or antagonist effects on estrogen receptors through ligand-induced conformational changes that govern coactivator or corepressor recruitment. This biochemical selectivity underlies their tissue-specific pharmacological actions. In the vasculature, SERMs modulate endothelial nitric oxide synthase (eNOS) activity, attenuate vascular smooth muscle cell (VSMC) proliferation, and regulate oxidative stress pathways, while also influencing platelet reactivity through NADPH oxidase–dependent mechanisms. Among the most studied SERMs are Tamoxifen and Raloxifene. Tamoxifen functions as a prodrug, requiring hepatic bioactivation, primarily by CYP2D6 and CYP3A4, to form active metabolites, notably 4-hydroxytamoxifen and endoxifen, with enhanced receptor affinity. In contrast, raloxifene undergoes extensive glucuronidation, resulting in low systemic bioavailability of the active compound. However, the systemic concentrations achieved are sufficient to confer measurable vascular effects. Despite these pharmacokinetic differences, both agents improve lipid and fibrinogen profiles, but also increase venous thromboembolism risk through modulation of coagulation pathways. Clinical trials confirm benefits in oncology and bone health, yet fail to demonstrate consistent reductions in cardiovascular endpoints. The pharmacological profile of SERMs therefore reflects a delicate equilibrium between receptor-mediated vascular protection and thrombotic liability. Indeed, their raison d’être increasingly extends beyond oncology into cardiovascular endocrine pharmacology, where they serve as prototypes for designing next-generation agents with optimized receptor selectivity and safer vascular outcomes.